2017
DOI: 10.1111/ger.12271
|View full text |Cite
|
Sign up to set email alerts
|

Oral flora in acute stroke patients: A prospective exploratory observational study

Abstract: Objective: To describe the bacterial profile of the oral flora during the first 2 weeks following a stroke, examining changes in the condition of the oral cavity and infections.Background: Dysphagia is common after a stroke and can lead to aspiration pneumo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 56 publications
4
23
0
Order By: Relevance
“…While there is limited knowledge on the prolonged effects of astrocyte activation poststroke in humans, GFAP blood concentrations have been associated with stroke severity and long-term functional outcome [48]. The combination of sustained neuroinflammation and systemic immunosuppression leaves stroke patients vulnerable to infection [49]. Therefore, we speculate that it was these prolonged neuro-inflammatory effects that contribute to the functional deficits we observed in our mice post-stroke.…”
Section: Cells and Significant Increases In Cd4+ T Cells And Cd8+ T mentioning
confidence: 83%
“…While there is limited knowledge on the prolonged effects of astrocyte activation poststroke in humans, GFAP blood concentrations have been associated with stroke severity and long-term functional outcome [48]. The combination of sustained neuroinflammation and systemic immunosuppression leaves stroke patients vulnerable to infection [49]. Therefore, we speculate that it was these prolonged neuro-inflammatory effects that contribute to the functional deficits we observed in our mice post-stroke.…”
Section: Cells and Significant Increases In Cd4+ T Cells And Cd8+ T mentioning
confidence: 83%
“…Boaden et al . recently described the bacterial profiles of the oral cavities of 50 patients during the first 2 weeks following stroke but found no associations between particular phylotypes and infections, concluding that their study may support larger observational studies ( 19 ).…”
Section: Introductionmentioning
confidence: 93%
“…In contrast, some studies have shown that improvement of oral care regimens in stroke patients can reduce incidence of stroke-associated pneumonia (18)(19)(20)(21). Boaden et al recently described the bacterial profiles of the oral cavities of 50 patients during the first 2 weeks following stroke but found no associations between particular phylotypes and infections, concluding that their study may support larger observational studies (19).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The health risk to individuals with swallowing difficulties is often compounded by impaired physical and cognitive function, which may impact further on the eating process. Decreased levels of alertness, fatigue, inability to maintain trunk and head alignment, reduced postural stability and tone, limb and body apraxia, visual perceptual difficulties, communication problems, a lack of insight, depression and poor oral hygiene (Boaden et al 2017), can all affect eating, drinking and swallowing of food, fluids and medication.…”
Section: Full Textmentioning
confidence: 99%